Bioelectronics with Topological Crosslinked Networks for Tactile Perception - Mingqi Ding; Pengshan Xie; Johnny C. Ho (Advanced Physics Research)
Abstract Bioelectronics, which integrate biological systems with electronic components, have attracted significant attention in developing biomimetic materials and advanced hardware architectures to enable novel information‐processing systems, sensors, and actuators. However, the rigidity of conjugated molecular systems and the lack of reconfigurability in static crosslinked structures pose significant challenges for flexible sensing applications. Topological crosslinked networks (TCNs) featuring dynamic molecular interactions offer enhanced molecular flexibility and environmentally induced reconfigurability, decoupling the competition between performances. Here, recent advances are summarized in assembly methods of bioelectronics with different TCNs and elaborate ion/electron‐transport mechanisms from the perspective of molecular interactions. Decoupling effects can be achieved by comparing distinct TCNs and their respective properties, and an outlook is provided on a new range of neuromorphic hardware with biocompatibility, self‐healing, self‐powered, and multimodal‐sensing capabilities. The development of TCN‐based bioelectronics can significantly impact the fields of artificial neuromorphic perception devices, networks, and systems.